Macroprudential Policies in Southeastern Europe - Dimova, Dilyana (IMF Working Papers; Working Paper ;, 2016)
This paper presents a detailed account of the rich set of macroprudential measures taken in four Southeastern European countries-Bulgaria, Croatia, Romania, and Serbia-during their synchronized boom and bust cycles in 2003-12, and assesses their effectiveness. We find that only strong measures helped contain domestic credit growth, the share of foreigncurrency- denominated loans provided by the domestic banking sector, or the domestic banking sector's reliance on foreign borrowing during the boom years. We also find that circumvention via direct external borrowing often fully offset the effectiveness of these strict measures, and thatmeasures taken during the bust had no discernible impact. We conclude that (i) proper calibration of macroprudential measures is of the essence; (ii) only strong, broad-based macroprudential measures can contain credit booms; (iii) econometric studies of macroprudential policy effectiveness should focus on measures rather than on instruments (i.e. classes of measures) and in so doing allow for possible non-linear and state-contingent effects.